The colonial encounter told twice; Parallel accounts of Carl Bock’s 1879 expedition to Borneo - Toivanen, Mikko (Wacana, Journal of the Humanities of Indonesia, 2024)
When the Scandinavian explorer Carl Bock, commissioned by the Dutch colonial authorities, undertook to make an expedition overland through Borneo in 1879, the island retained a sense of the exotic in the European imagination. Audiences were especially hungry for tales of the island’s headhunting Dayak inhabitants, a demand that Bock was happy to meet. In fact, he wrote two distinct narratives of the expedition: the Dutch-language report he had been tasked to write for the Dutch but also a longer, more entertainment-focused English-language travelogue for a broader audience. Comparing the two accounts, clearly based on the same underlying text but differing in many details and tone, provides critical insights into the unstable and unreliable nature of the colonial encounter as recounted in written sources. Such an analysis also reveals how these narratives were shaped retrospectively, to meet the expectations of different assumed audiences and quickly changing literary fashions.